THE PREVALENCE OF ANTIBIOTIC-RESISTANT STAPHYLOCOCCUS AUREUS ISOLATED FROM URINARY TRACT INFECTIONS IN SHEEP AND SHEEP BREEDERS - Areean Ibrahim Hassan Bak(1), Ali Ibrahim Ali Al-Ezzy(2), Al-Zubaidi Raad Mahmood Hussein(3) (Chelonian Research Foundation, 2023)
The objective of this research was to examine the prevalence of bacterial urinary tract infections in sheep and sheep breeders, as well as their antibiotic susceptibility. In Sulaymaniyah province (Kalar district and neighboring villages) and Diyala province (Khanaqin district, villages of Qorato district), 120 urine specimens from sheep and sheep breeders with urinary tract infections (UTIs) were collected from the first of October 2022 to March 2023. Current study includes (49) females sheep breeders and (71) ewes suffering from clinical signs of urinary tract infections. A total of 27/ 49, (55.10%) of urine specimens give positive urine culture among female sheep breeders versus 22 out of 49, (44.89%) give negative urine culture. A total of 35/71, (49.29%) of urine specimens gives positive urine culture among ewes versus 36 out of 71, (50.70%) give negative urine culture. Results showed that Staphylococcus aureus represent 3(4.83%), in Human, while in sheep S.aureus represent 7(11.29%), then their susceptibility to wards selected antibiotics were detected. Results appeared the S.aureus shown (100%) resistance for the following Class of antibiotics, Penicillines and Cephalosporins. Methicillin resistance was detected by Cefoxitin Screen test which indicate that 3/3, (100%) of S. aureus have resistance which confirmed early by detection of MecA gene. Resistance of S.aureus to Polypeptides antibiotics was detected in 3/3, (100%) for Vancomycin and 2/3, (66%) for Teicoplanin in female sheep breeders, while in sheep S.aureus shown (100%) resistance for the following Class of antibiotics, Penicillines and Cephalosporins. Methicillin resistance was detected by Cefoxitin Screen test which indicate that 7/7, (100%) of S. aureus have resistance which confirmed early by detection of MecA gene. Resistance of S.aureus to polypeptides antibiotics was detected in 7/7, (100%) for vancomycin and 6/7, (85.72%) for Teicoplanin. Resistance of S.aureus to macrolides antibiotics was detected in 1/7, (14.28%) for Azithromycin. Resistance of S.aureus to Lincosamides antibiotics, Clindamycin was detected in 1/7, (14.28%)